2022
DOI: 10.3847/1538-4357/ac498f
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of TESS Stellar Rotation Periods Using Deep Learning

Abstract: We used a convolutional neural network to infer stellar rotation periods from a set of synthetic light curves simulated with realistic spot-evolution patterns. We convolved these simulated light curves with real TESS light curves containing minimal intrinsic astrophysical variability to allow the network to learn TESS systematics and estimate rotation periods despite them. In addition to periods, we predict uncertainties via heteroskedastic regression to estimate the credibility of the period predictions. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 70 publications
0
43
0
Order By: Relevance
“…Strides are additionally being made in detecting long rotation periods from TESS light curves using more modern techniques such as machine learning (Lu et al 2020;Claytor et al 2022). An improved characterization of the TESS instrument as well as an improved understanding of scattered light across all TESS observing sectors will improve our ability to detect rotation signals beyond tens of days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strides are additionally being made in detecting long rotation periods from TESS light curves using more modern techniques such as machine learning (Lu et al 2020;Claytor et al 2022). An improved characterization of the TESS instrument as well as an improved understanding of scattered light across all TESS observing sectors will improve our ability to detect rotation signals beyond tens of days.…”
Section: Discussionmentioning
confidence: 99%
“…To correct and stitch together our light curves, we initially followed the methods performed in García et al (2011) on the Kepler sample. However, upon implementing this method on several simulated TESS light curves from Claytor et al (2022), we found that these methods preserved too many TESS-specific systematics for us to accurately measure rotation periods. In light of this, we devise our own method to correct for TESS systematics while preserving any possible rotation signals.…”
Section: Processing Tess Light Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting, nearly year-long light curves were processed to remove data affected by systematics. This processing, however, is still far from perfect, with TESS systematics not yet well enough understood for confident measurement of P rot longer than roughly half the length of a sector, or ≈15 days (Claytor et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, as was highlighted recently by Claytor et al (2022), there are fundamental issues with trying to measure longer P rot with TESS light curves produced by stitching together data from several 27 day sectors. In the resulting light curves, it is difficult to assess whether a signal is caused by true fluctuations in stellar brightness, or whether it is a result of systematics in the data either incorrectly removed or added in the processing of the light curves.…”
Section: Measuring Rotation Periodsmentioning
confidence: 99%